Health Care as a Factor of Life Satisfaction and Quality of Life of Ukrainians During the COVID-19 Pandemic - Chykhantsova, Olena (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2022)
The article presents an analysis of the problem of medical services and the quality of medical care to the population of Ukraine and their impact on life satisfaction and quality of life during the Covid-19 pandemic. The main aim of the study is to quantify the impact of various factors on health and life satisfaction, as well as satisfaction with medical services. The respondents completed an author's questionnaire, which includes assessment of life satisfaction and assessment of subjective quality of life. Data were collected from 385 people from different regions of Ukraine, different in profession, in age between 16 to 65. The results of the study present that the quality of life during quarantine among Ukrainians has decreased. It was found that the majority of Ukrainians surveyed are also dissatisfied with the quality of care for junior medical staff. It has been studied that people's financial and health conditions before quarantine directly affected satisfaction and quality of life during the Covid-19 pandemic. Relationships between scales of happiness, quality of life and life satisfaction have been identified. Satisfaction is an important indicator of the quality of health care. The results suggest that Ukrainians need more medical care, ranging from prevention, treatment, referral and rehabilitation during the Covid-19 pandemic. It was found that timely and high-quality medical services were complicated during the pandemic. In order to provide quality medical services, it is also necessary to take into account such factors as the method of providing medical care, as well as factors that are part of the health care system.
Keywords: life satisfaction; medical services; Covid-19; quality of life